Clinical diagnosis and histological analysis of vocal nodules and polyps - Nunes, Raquel Buzelin; Behlau, Mara [UNESP]; Nunes, Mauricio Buzelin; Paulino, Juliana Gomes (My University, 2013)
Recent studies emphasize the importance of the clinical-histology correlation in laryngeal pathologies. Objective: To compare the ENT diagnosis with the pathology diagnosis one of 132 surgical specimens, from 119 patients with vocal nodules and polyps. Method: Retrospective study. We investigated the paraffin blocks corresponding to the lesions of the operated patients. We made new histology cross-sections, totaling 396 new slides, divided into three groups: hematoxylin and eosin, Gomori trichrome and PAS. We analyzed the following histological parameters: epithelium, lamina propria, basement membrane, vascular changes. We compared the laryngological and pathological diagnoses, and we did the statistical analysis, checking the predominant histological aspects in each lesion. Results: There was an agreement between the clinical and pathological diagnoses in 123 (93.18%) of 132 lesions analyzed (42.42% nodules and 50.76% polyps). In the histological parameters we found: epithelial changes such as nodules hyperplasia (82.14%) and polyp atrophy (31.34%). Lamina propria: edema in polyps (71.43%), fibrosis in the nodules (57.14%). Basement membrane: thickened nodules (100%), thin/no change in polyps (100%). There was a predominance of vascular changes in the polyps. Conclusion: We found a high correlation between the ENT diagnosis and the pathology report. Histopathologically, the nodules presented with predominantly epithelial changes, lamina propria and basement membrane fibrosis, while the polyps by changes strictly on the lamina propria and vascular aspects.
Keywords: Histology; Otolaryngology; Voice